2007
DOI: 10.1002/jor.20370
|View full text |Cite
|
Sign up to set email alerts
|

Periarticular ligament changes following ACL/MCL transection in an ovine stifle joint model of osteoarthritis

Abstract: Anterior cruciate ligament (ACL) injuries often lead to significant functional impairment, and are associated with increased risk for induction of degenerative joint disease. However, few studies have described the effect of ligament transection on the remaining intact knee ligaments. This study sought to determine specifically what impact combined ACL/medial collateral ligament (MCL) transection had on the remaining intact knee ligaments, particularly from the histological, biochemical, and molecular perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…At 20 weeks after ACL/MCL transection, the cut ends of the ACL remained separate, but the cut ends of the MCL were bridged by scar (Funakoshi et al, 2007). Hypotheses to explain the differential healing capacity of the ACL and MCL include differences in blood supply (Bray et al, 2003a), vascular and metabolic response to injury (Bray et al, 2003a;Nagineni et al, 1992), and intra-articular vs. extra-articular location (Spindler et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…At 20 weeks after ACL/MCL transection, the cut ends of the ACL remained separate, but the cut ends of the MCL were bridged by scar (Funakoshi et al, 2007). Hypotheses to explain the differential healing capacity of the ACL and MCL include differences in blood supply (Bray et al, 2003a), vascular and metabolic response to injury (Bray et al, 2003a;Nagineni et al, 1992), and intra-articular vs. extra-articular location (Spindler et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…A small number of studies have demonstrated that ACL deficiency results in biological changes in adjacent ligaments (Funakoshi et al, 2007;Zachos et al, 2002). At 20 weeks after ACL/MCL transection, the cut ends of the ACL remained separate, but the cut ends of the MCL were bridged by scar (Funakoshi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is an increasing interest in the early detection of OA in order to possibly slow and/or stop its progression. Most animal model studies have demonstrated a delayed development of OA after severe injuries to the joint [24][25][26]. The degeneration of cartilage is a slow process and is observed only after 20 weeks following anterior cruciate ligament (ACL)/ medial collateral ligament (MCL) transection in an ovine model.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical analyses were conducted of 1) hydroxyproline (Hyp), an imino acid marker used as an index of total collagen content measured by HPLC, 2) the mature collagen cross-link hydroxylysylpyridinoline (HP), which improves ECM strength and tissue quality in healing ligaments, also measured by HPLC, and 3) MCL cellularity by DNA measurement to assess the state of cell proliferation in the healing ligament. Real-time quantitative PCR gene markers were used to determine the upregulation or downregulation of specific genes that impact the ECM in healing MCLs as previously determined (15,18,19,32,34). To assess new collagen synthesis in remodeling ligament, the genes encoding collagen type I (Col1A2), collagen type III (Col3A1), and collagen type V (Col5a1) were assayed.…”
mentioning
confidence: 99%